Subjective Well-Being in Nursing and Midwifery Students of Golestan University of Medical Sciences - Zahra Sabzi; Hamideh Mancheri; Zahra Royani; Mohammad Aryaie; Seyedyaghoob Jafari; Ghorbanali Ahmadi (Golestan University of Medical Sciences, 2015)
Background and Objective: Subjective well-being, a field of positive psychology, attempts to assess the cognitive and emotional lives. Given the fact that nursing and midwifery students are exposed to stress in clinical settings, we aimed to assess subjective well-being to promote educational programs. Material and Methods: This across-sectional study was conducted on 104 nursing and Midwifery students selected via simple random sampling, 2013. The instruments, filled out by students, were a demographic checklist and Kyeez subjective well-being questionnaire consisting of three domains of emotional, social and psychological. We used mean and standard deviation for data description and T-test and ANOVA for analysis. Results: The mean score of subjective well-being was 203.20 in nursing and 210.21 in midwifery students. In nursing students, the Mean score in emotional, psychological and social domain was 44.05, 93.40 and 65.74, respectively, and it was 45.72, 94.78 and 69.55, respectively in midwifery students. Gender was the only variable associated significantly with subjective well-being of nursing students (P>0.05). Conclusion: Given the high score of subjective well-being and that of its domains, we recommend applying some educational programs with the consideration of emotional, psychological and social aspect of students.